Identification and Characterization of Hemagglutinating Viruses in Native Chickens in Bangladesh - Nooruddin, G.M.; Rahman, M.T.; Mohammad, M.; Rahman, M.M. (International Journal of Poultry Science, 2007)
A total number of 224 cloacal swabs were examined for hemagglutinating activity from 4 different poultry farms of Noakhali district in Bangladesh. Out of the total samples 15 exhibited positive reactions with chicken erythrocytes. Among the 15 positive samples, 11 were found to be positive for Newcastle disease virus. The highest (100%) prevalence of Newcastle disease virus was found in Ram Nagar union and the lowest (66.66%) were found in Rajapur union. Seventy five percent prevalence was found in Jaylashker and Matubhuyian union. The overall prevalence of Newcastle disease virus was found to be 79.17% in the four unions. No egg drop syndrome virus and avian influenza viruses were identified in the samples those gave positive result in hemaggluntination test.